Impact of Eyjafjallajökull on tourism and international flights - Anita Anna Jónsdóttir 1979- (2011)
Iceland has frequent volcanic eruption however the extent of the disruption on aviation caused by Eyjafjallajökull eruption between March to May was unexpected. Passengers all over Europe was affected either by planes getting, delayed, rescheduled or canceled. Visitation numbers in Iceland declined fast in relation to the disruption caused on airline operation, which can have damaging effect on businesses and economies reliant on the income generated from tourists. The aim was to assess Icelandic airline operations affected by Eyjafjallajökull’s eruption in relation to tourist arrivals. The research is based on semi-open questions taken by the primary airlines in Iceland, Icelandair and Iceland Express and numerical data collected from EUROCONTROL and Icelandic Tourist Board. Arrivals and departures dropped by half during 15th-28th of April. However, the airlines continued operations. The solution was relocation with flights embarking from alternative cities, such as Akureyri in the north and Egilsstaðir in the east. Tourist numbers dropped around 17,5% in April and May. Icelandair estimates losing about 20% of scheduled flights and rescheduled 180 flights, and Iceland Express lost about 100 flights in relation to the eruption. However, the effects on tourist were not significant, with increased numbers shortly after the eruption ceased. Oft hafa orðið eldgos á Íslandi þá aldrei hefur röskun flugs verið eins mikil eins og við eldgosið í Eyjafjallajökli á milli Mars og Maí. Farþegar um alla Evrópu urðu fyrir áhrifum vegna tafa, niðurfellingum eða endurbókunar á flugi. Fjöldi ferðamanna fækkaði mjög hratt með truflunum á flugumferð, sem gæti haft skaðleg áhrif á viðskipti og hagkerfi sem reiðir sig á tekjur ferðamanna. Markmiðið var að meta áhrif eldgosins í Eyjafjallajökli á flugrekstur í tengslum við komur ferðamanna tíl Íslands. Ransóknin er byggð á hálf opnum spurningum sem tekin voru af aðal flugfélogunum á Íslandi, Icelandair og Iceland Express og tölulegum gögnum tekið saman frá EUROCONTROL og ...